Diabetic diarrhoea: A study on gastrointestinal motility, pH levels and autonomic function. (7th July 2021) - Sangnes, Dag A.; Dimcevski, Georg; Frey, Jakub; Søfteland, Eirik
Abstract: Background: Chronic diarrhoea is a common, but poorly investigated diabetes complication. Autonomic neuropathy is a leading pathophysiological theory founded on old, small studies. Studies of gastrointestinal motility and pH levels are lacking. Objectives: Using new diagnostic methods, we aimed to find out if diabetic diarrhoea was associated with alterations in gastrointestinal motility, pH levels and autonomic function. Methods: Fifty‐seven patients (42 women, 46 with type 1 diabetes) were prospectively included. Symptoms were evaluated with the gastrointestinal symptom rating scale, defining ≥4 points as cases with diarrhoea. Patients scoring <4 were used as controls. We used the wireless motility capsule to measure gastrointestinal transit times, pH levels and contractility parameters. Autonomic function was assessed by measuring heart rate variability, baroreflex sensitivity and orthostatic hypotension. Results: Seventeen patients (30%) had diarrhoea. Compared with controls, cases had slower gastric emptying (21:46 vs. 4:14, h:min, p = 0.03) and faster colonic transit (18:37 vs. 54:25, p < 0.001). Cases had increased intraluminal pH in the antrum (2.4 vs. 1.2, p = 0.009), caecum (7.3 vs. 6.4, p = 0.008) and entire colon (7.1 vs. 6.7, p = 0.05). They also had a decreased pH difference across the pylorus (3.3 vs. 4.9, p = 0.004) and ileocaecal junction (0.6 vs 1.0, p = 0.009). The groups did not differ in autonomic function, but diastolic blood pressure drop correlated rs = −0.34 ( p = 0.04) with colonic transit time. Conclusions: Patients with diabetic diarrhoea had altered gastrointestinal transit and intraluminal pH levels, but minimal changes in autonomic function. Our results suggest that tests of gastrointestinal function are clinically useful in diabetic diarrhoea. Abstract :